Water quality and water borne diseases in lowland ecosystem of Banyuasin, South Sumatra, Indonesia - Dianita Ekawati; Tan Malaka; Robiyanto H. Susanto; M. T. Kamaluddin; Dwi Setyawan (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Water quality and quantity is always an important issue in lowland ecosystem of Banyuasin. Low domestic water supply sanitation is considered as having an important contribution on the high frequency of waterborne diseases in the area. The study aims at recording water borne diseases and the water quality in the lowland area of Banyuasin District. This field research was conducted using a cross-sectional method. Total samples were 210 households in Telang which were observed during July through August 2011. Six water samples were measured for their physical and chemical properties, in addition to 1 water sample for bacteriological test. All respondents used river water for sanitary purposes and 41.4% of them also have dug wells. Those who used river water for sanitation, 68.5 % also consumed purified water for drinking purpose. All water samples are acidic (pH 5,68-6,19) and contain high Iron  (1-26,269 Mg/L). Water has yellowish color.  The major disease are diarrhea and skin diseases. In the lowland area with the estuarine ecosystem water quality and scarcity are serious problems. This in turn causes the high prevalent of waterborne diseases such as diarea. Low level of education and socio-economic status make it difficult for the local people to overcome these problems. Outside intervention especially government so as to improve the condition is needed